Good Governance in Corporate Social Responsibility (C.S.R.) Program at Siak Regency - Zainal, Zainal; Zeriand, Deby (SCAD Independent, 2022)
The fundamental problem of this research is the lack of transparency and accountability of the Regional Development Planning Agency (BAPPEDA) with P.T.IKPP disseminates the corporate social responsibility (C.S.R.) program to the people of the Siak Regency. This study aimed to determine the implementation of good governance in the corporate social responsibility (C.S.R.) program by the Regional Development Planning Agency (BAPPEDA) in Siak Regency. The research method used in this study uses a qualitative method with a purposive sampling technique. The study results indicated that good governance in the corporate social responsibility (C.S.R.) program is not running optimally due to the incompatibility between implementation in the field and the principles used in good governance, namely participation, transparency, accountability, and the rule of law. This study's conclusion showed the lack of collaboration from BAPPEDA with all stakeholders involved in providing reports on planned programs and even those that have been realized. Accountability and transparency activities were less than optimal in socializing with the people of Siak Regency. This research suggests that P.T. IKPP maximizes its role in providing information to the people of the Siak Regency. BAPPEDA must further increase its duties in supervising the company's implementation of C.S.R. in the community.